151k views
5 votes
HIGHSCHOOL ALGEBRA!!!!! PLS HELP :)

Find the root of the equation: (6x–1)(6x+1) - 4x(9x+2) = −1

User Mariusnn
by
4.8k points

1 Answer

5 votes

(6x–1)(6x+1) - 4x(9x+2) = −1

Simplify the left side:

36x^2-1 -36x^2-8x = -1

Combine like terms:

-1 -8x = -1

Add 1 to both sides:

-8x = 0

Divide both sides by -8:

x = 0 / -8

x = 0

The root is 0

User Bbodenmiller
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.